Analysis of Airway Management for Cesarean Delivery: Use of Risk and Proportion Differences. Issue 3 (March 2022) - King, Andrew; Morello, Justin; Clark, Allison; Ray, Adrienne; Martel, Colleen; McLendon, Roneisha; McConville, Anne; Russo, Melissa; Germond, Liane; Nossaman, Bobby
Abstract: Objectives: Securing the parturient airway is essential during general anesthesia for cesarean delivery. The purpose of this study was to compare inferior airway views provided by the use of three commonly available laryngoscopy blades—Macintosh, Miller, or Glidescope Mac-Style—to the incidence of difficult orotracheal intubation. Methods: Following institutional review board approval, data from 449 electronic medical records in parturients undergoing general anesthesia for cesarean delivery were extracted during a 6-year period. The association of these blades with difficult orotracheal intubation was analyzed with risk and proportion differences measures of effect size. Results: The overall incidence of difficult orotracheal intubation was 4.2% (95% confidence interval 2.7 − 6.5%), with 6 failed orotracheal intubations (5 laryngeal mask airways rescues and 1 mask rescue). Clinically important increases in risk differences for difficult orotracheal intubation were observed in parturients with restricted mouth openings, modified Mallampati III and IV views, and reduced thyromental distances. When modified Cormack-Lehane views were grouped into III and IV versus I and II cohorts; proportion differences for difficult orotracheal intubation were dependent upon the type of blade used, with the Miller blade providing the lowest proportion difference. Conclusions: Miller blade laryngoscopy provided the lowest proportion difference for difficult orotracheal intubation during general anesthesia for cesarean delivery. Miller blade laryngoscopy provides effective procurement of the parturient airway. Abstract : The rate of difficulty with orotracheal intubation in obstetrics has remained unchanged during the past 4 decades, with little comparative information on the use of measures of effect size for the type of laryngoscope blade used in airway management during general anesthesia for caesarean delivery. The purpose of this study was to calculate the risk and proportion differences in the incidences of difficult orotracheal intubation with three commonly used laryngoscope blades in parturients undergoing general anesthesia for caesarean delivery.